2018
DOI: 10.1038/s41598-017-18427-2
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of insulin resistance by PGE1 via autophagy-dependent FGF21 pathway in diabetic nephropathy

Abstract: Insulin resistance is a critical process in the initiation and progression of diabetic nephropathy (DN). Alprostadil (Prostaglandin E1, PGE1) had protective effects on renal function. However, it is unknown whether PGE1 inhibited insulin resistance in renal tubule epithelial cells via autophagy, which plays a protective role in DN against insulin resistance. Insulin resistance was induced by palmitic acid (PA) in human HK-2 cells, shown as the decrease of insulin-stimulated AKT phosphorylation, glucose transpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(53 citation statements)
references
References 56 publications
2
51
0
Order By: Relevance
“…Therefore, our Here, we found that PGE1 mimicked the role of rapamycin on the phenotypic switching and was dramatically counteracted by 3-methyladenine. Our previous study demonstrated that inhibiting autophagy was responsible for the enhancement of FGF21 by PGE1 in palmitic acid-treated HK-2 cells [9]. The current study further demonstrated that autophagy was a new pharmacological target.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…Therefore, our Here, we found that PGE1 mimicked the role of rapamycin on the phenotypic switching and was dramatically counteracted by 3-methyladenine. Our previous study demonstrated that inhibiting autophagy was responsible for the enhancement of FGF21 by PGE1 in palmitic acid-treated HK-2 cells [9]. The current study further demonstrated that autophagy was a new pharmacological target.…”
Section: Discussionsupporting
confidence: 72%
“…PGE1 also had a significant role in glucose and lipid metabolism in patients with T2DM. Our recent study showed that PGE1 could protect renal function via autophagy in diabetic nephropathy [9]. However, it has not been reported whether PGE1 has the potential protection on the phenotype in VSMCs via autophagy pathway.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…The decreased plasma Pi and increased urinary Pi excretion in mice after adminstration of TB-11, the active and functional peptide of beclin 1 futher proves the concept that high autophagy in the kidney promotes negative Pi balance. The restored body growth and reduced mortality in BK/BK;kl/kl mice was abolished by high-Pi diet further The role of autophagy in regulation of renal transport 66,67 including water, 68,69 glucose, 70 cysteine, 71 and other electrolytes 72 have been reported. The current manuscript provides new data linking autophagy with phosphate transport in the renal tubules.…”
Section: Autophagy Affects Phosphate Homeostasis Through Induction mentioning
confidence: 90%
“…The HE staining was performed as described previously [48]. Brie y, hearts were removed from the rats and xed with 4% paraformaldehyde overnight, and then embedded in para n. The prepared sections were sliced to 8 µm thick and stained with hematoxylin and eosin (HE).…”
Section: He Staining Analysismentioning
confidence: 99%